'How I edit my Instagram images': investigating skilled vision in the work of YouTube's lifestyle-content creators. - ROIVAINEN, IDA (Visual Studies, 2025)
Woman social media content creators' visual expertise is ill understood and arguably overlooked. Through the example of lifestyle-creators, this article explores the ways they plan, produce, and look at imagery on Instagram and YouTube, and shows that creators have specific ways to learn, communicate, and take part into social practices that are key in formulating their skilled vision and visual professionality. The study is part of a larger nethnographic project in which lifestyle-YouTube channels and related social media platforms have been studied for three years. In this article, online observation of 13 creators and content analysis of instructional 'how I edit' – videos show, that creators have trained sense of vision that involves everyday work practices common both for amateur and professional photography practitioners. The findings suggest that creators' skilled vision is produced through four processes: (1) sharing expertise; (2) the use of specific technology and software; (3) routine; (4) creativity. Finally, it is argued that investigating creators' skilled vision adds to our understanding of the mechanisms that have excluded a great deal of 'feminine' creativity from our historical and present accounts. I situate lifestyle creators within a longer tradition of women engaging with photography, photographic technologies, and product advice, and offer ways for understanding digitally networked 'influencing' and visual practices on social media today.